Age‐based inter‐subject variability in platelet and white blood cell concentrations of platelet‐rich plasma prepared using a new application to blood separation system - Trevisson, Bibiana; Becerro‐de‐Bengoa‐Vallejo, Ricardo; Sevillano, David; González, Natalia; Losa‐Iglesias, Marta; López‐López, Daniel; Alou, Luis (International wound journal, 2022)
The benefit of autologous platelet‐rich plasma (PRP) treatment is still under discussion. Variations in PRP products, consequence of the lack of a standardised protocol for the multitude of commercially available blood separation systems and the lack of knowledge of the optimal composition of PRP or its suitability for the proposed indication are some of the reasons behind clinical inconsistencies. The impact of inter‐subject variability in PRP has received less attention in comparison. The purpose of this study was to determine the inter‐subject variability, based on age, in the concentrates prepared by a new blood concentration system. Twenty‐six healthy volunteers of both genders (29‐93 years) were enrolled. Whole blood (WB) was collected from each participant to prepare PRP using the Easy PRP kit. Platelets and white blood cells (WBC) from WB and PRP were analysed after split population by age; patients younger than 65 years (n = 13) and patients ≥65 years old (n = 13). Among the demographic characteristics tested, only age was significantly different between the groups. Cell capture efficiency of the system was specific for each type of blood cell and identical for both age groups. Platelets and WBC in PRP were higher than in WB (P < .001). In WB, platelets and WBC concentrations were significantly lower in older group (P ≤ .035). These differences persisted in the prepared PRP (P ≤ .004). The ageing of population has a strong influence on the haematocrit and therefore on the composition of PRP. Because the efficiency of blood separator system seems to be constant across individuals, the inter‐subject haematocrit variability based on age could be used as a predictor of resulting PRP. The clinical application of PRP should be restricted to the specific cell capture capacity of the different commercial devices.